EFFECT OF SCATTERER DISTRIBUTION ON RANDOM LASER MODEL USING OPTI-FDTD - Adavize, Momoh Hameed; Ahmed, Mohammed (FUDMA Journal of Sciences, 2025)
Random lasers, unlike conventional lasers, rely on multiple scattering in a disordered gain medium to achieve optical feedback, making scatterer distribution a crucial factor in their performance. This study investigates the effect of scatterer distribution on random laser performance using the Optical Finite-Difference Time-Domain (Opti-FDTD) simulation tool. The primary objective is to examine how varying scatterer densities—low, medium, and high—affect key lasing parameters, including lasing threshold, emission spectrum, and spatial coherence. Methodologically, the study involves designing photonic bandgap (PBG) structures, systematically varying scatterer arrangements, and analysing the resulting optical behaviours through simulation. Key findings indicate that medium-density scatterer configurations achieve the lowest lasing threshold and the most well-defined emission spectra, offering an optimal balance between light feedback and scattering losses. High-density distributions enhance spatial coherence due to stronger light localization but introduce higher thresholds and spectral overlap, while low-density configurations suffer from weak feedback and reduced performance metrics. The results align with theoretical predictions and experimental data, emphasizing the critical role of scatterer distribution in optimizing random laser designs. These insights hold significant implications for developing more efficient random lasers for applications in imaging, spectroscopy, sensing, and energy-efficient lighting.